The Patterns of Oral Diseases among Type 2 Diabetes Mellitus Patients Attending at National Healthcare Network (NHN) Mirpur Centre, Dhaka, Bangladesh (Bangladesh Journal of Dental Research & Education, 2013)
Background: The term diabetes mellitus describes a group of disorders characterized by elevated levels of glucose in the blood and abnormalities of carbohydrate, fat and protein metabolism. A number of oral diseases and disorders are associated with diabetes mellitus and, gingivitis and periodontitis have been identified as possible risk factors for poor metabolic control in subjects with diabetes. Objective: To assess oral diseases in type 2 diabetes mellitus patients and controls who attended at National Healthcare Network (NHN), Mirpur Centre, Dhaka, Bangladesh. Materials & Methods: A total of 100 subjects - 47 diabetics and 53 non-diabetics fulfilled the eligibility criteria were selected consecutively. Pretested semi-structured interviewer administered questionnaire and check list were utilized to assess the main objective of the study. Cross tabulations and associations were found out by using Chi-square Test  Statistical Package for the Social Sciences was used for data analysis. Results: The cases were relatively older than the controls with mean age of the subjects in case group being significantly higher than that in the control group (p < 0.001), but the groups were not statistically different in terms of sex (p = 0.194). More than two-thirds (68.1%) of the cases and 52.8% of the controls exhibited burning mouth syndrome (p = 0.120). Candidiasis and dental caries were associated, more than in case control group (p = 0.020 and p < 0.001 respectively). Gingivitis was found significantly higher in case group compared to control group (78.7% vs. 37.7%, p < 0.001). In the case group, nearly half (48.9%) had periodontitis, 29.8% alveolar bone loss and 27.7% collagen metabolism, as opposed to none in the control group (p < 0.001). Conclusion: Oral diseases are multi-factorial and the factors responsible for these diseases are preventable. Dentists must be familiar with techniques to diagnose, treat and prevent oral diseases in patients with diabetes. DOI: http://dx.doi.org/10.3329/bjdre.v3i2.16602 Bangladesh Journal of Dental Research & Education Vol.3(2) 2013: 5-11